2020
DOI: 10.1155/2020/1035182
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-Guided Transmuscular Quadratus Lumborum Block Reduces Postoperative Pain Intensity in Patients Undergoing Total Hip Arthroplasty: A Randomized, Double-Blind, Placebo-Controlled Trial

Abstract: Background and Objectives. Pain management following total hip arthroplasty (THA) has been widely investigated; however, the best effective method is yet to be determined. The aim of this prospective, placebo-controlled study was to evaluate the analgesic efficacy of ultrasound-guided QL3 block in patients undergoing THA. Methods. Eighty-eight patients undergoing THA were randomized to receive 0.33% ropivacaine (Group QLB, n = 44) or saline (Group Con, n = 44) for QL3 block. Spinal anesthesia was then performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
54
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(57 citation statements)
references
References 32 publications
(36 reference statements)
1
54
0
Order By: Relevance
“…The weakness of lower extremities was identified in patients receiving QLB-TM. Previous studies indicated that the QLB-TM reduced postoperative 24 h pain scores and opiates consumption in patients after total hip arthroplasty [21]. The lower extremities weakness was accidentally reported in patients receiving QLB-TM [22].…”
Section: Discussionmentioning
confidence: 95%
“…The weakness of lower extremities was identified in patients receiving QLB-TM. Previous studies indicated that the QLB-TM reduced postoperative 24 h pain scores and opiates consumption in patients after total hip arthroplasty [21]. The lower extremities weakness was accidentally reported in patients receiving QLB-TM [22].…”
Section: Discussionmentioning
confidence: 95%
“…Eighteen articles were selected for full-text analysis. Of them, thirteen studies fulfilled the inclusion criteria and were analyzed in this review (21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33).…”
Section: Details Of Included Studiesmentioning
confidence: 99%
“…Details of the included studies are presented in Table 1. Nine (21,24,26,(28)(29)(30)(31)(32)(33) were RCTs while four (22,23,25,27) were retrospective studies. Most studies were carried out in the USA or China.…”
Section: Details Of Included Studiesmentioning
confidence: 99%
“…The quadratus lumborum (QL) block was first described in 2007, 6 and since has been used to reduce pain and narcotic use in a wide variety of surgeries including Cesarean section, hip arthroplasty, and laparotomy. 7 , 8 , 9 , 10 In laparoscopic donor nephrectomy, repeated QL block has shown comparable postoperative pain scores and sensory blockade to continuous epidural analgesia. 11 …”
Section: Introductionmentioning
confidence: 99%
“…The quadratus lumborum (QL) block was first described in 2007, 6 and since has been used to reduce pain and narcotic use in a wide variety of surgeries including Cesarean section, hip arthroplasty, and laparotomy. [7][8][9][10] In laparoscopic donor nephrectomy, repeated QL block has shown comparable postoperative pain scores and sensory blockade to continuous epidural analgesia. 11 We hypothesized that administering a long-acting bupivacaine transmuscular QL block could improve postoperative pain control and promote faster return to normal activities in patients undergoing laparoscopic donor nephrectomy at our institution.…”
Section: Introductionmentioning
confidence: 99%